STUDY OF THE USE OF THE THREE LEVELS OF THINKING AND REPRESENTATION - Stojanovska, Marina; M. Petruševski, Vladimir; Šoptrajanov, Bojan (Macedonian Academy of Sciences and Arts, 2017)
As is well-known, the chemical knowledge is acquired at three levels: the macroscopic and tangible (what can be seen, touched and/or smelt); the sub-microscopic (atoms, molecules, ions and structures) and the representational (symbols, formulae, equations, mathematical manipulation, graphs etc.). In order to acquire real knowledge, all factors involved in the educational process (authors of textbooks, teachers, electronic sources of information and students) should do everything possible to avoid formation of school-made erroneous notions (misconceptions). Reported here are the findings of a study on the presence of students’ misconceptions regarding the three levels of representation in the chemistry teaching in the Republic of Macedonia. As our study showed, many school-made misconceptions are due to the fact that students do not distinguish between the three levels of think-ing/representation.